(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetes mellitus is a chronic condition requiring consistent self-management and medication adherence to prevent complications. Nonadherence to antidiabetic regimens remains a global challenge, leading to increased morbidity and healthcare costs. Aim: This systematic review examined the effectiveness of nurse-led educational interventions in improving medication adherence among adults with diabetes mellitus. Methods: Guided by PRISMA 2020 standards, a systematic search was conducted across PubMed, Scopus, CINAHL, Web of Science, and Google Scholar. Ten studies published between 2007 and 2025 were included. Eligible designs were randomized controlled trials, quasi-experimental, or pre–post studies assessing adherence, HbA1c, or self-efficacy outcomes. Results: Nurse-led interventions demonstrated significant improvements in medication adherence (8–32%), HbA1c reduction (0.23–0.4%), and self-efficacy across diverse populations. Personalized education, follow-up counseling, and family participation enhanced sustained adherence. Telephonic and web-based models showed comparable benefits in urban and resource-limited settings. Conclusion: Nurse-led educational programs are clinically effective, culturally adaptable, and economically feasible strategies for improving diabetes medication adherence and glycemic control. Future research should focus on standardizing outcome measures and long-term adherence trajectories.